Time Variation in the Chemical and Isotopic Composition of Fumarolic Gasses at Kusatsu-Shirane Volcano, Japan - Ohba, Takeshi; Yaguchi, Muga; Nishino, Kana; Numanami, Nozomi; Tsunogai, Urumu; Ito, Masanori; Shingubara, Ryo (Frontiers in Earth Science, 2019)
At Kusatsu-Shirane volcano Japan, the intense seismic activity took place in 2014 and 2018. To investigate the relationship between the activity and the chemistry of fumarolic gas, the gas samples have been repeatedly analyzed. A monotonic decrease in CO2/H2O, He/H2O and N2/H2O ratios since July 2014 to November 2017 suggests the decline of magmatic component. On contrary CH4/H2O ratio significantly increased during the seismically quiet period, suggesting the reduced condition in hydrothermal system favoring to the formation of CH4. The high N2/He ratio in the quiet period suggests the addition of component originating in crustal rock hosting hydrothermal system. The N2/He ratio in 2018 was definitely lower than the ratio in 2014, indicating the evolution of magma brought by the degassing. The δD(H2O), δ18O(H2O) and CO2/H2O ratio of fumarolic gas were modeled with the following processes; the generation of vapor phase after the mixing between magmatic gas and a cold groundwater with meteoric origin, the addition of vapor phase with meteoric origin, and the partial condensation of water vapor near surface. Only a single magmatic gas is necessary for the above modeling.